POLA PERTUMBUHAN AYAM KAMPUNG LOKAL PERIODE STARTER PADA PEMELIHARAAN INTENSIF - Rajab Rajab (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2018)
Growth, which is defined as an increase in body size per unit time, is one of the most important characteristics of farm animals. The purpose of this research was to know and analysis the growth pattern of native fowl ranging in intensive farming system. Animals used in this study consists 101 native fowls which measured in 8 weeks of age to defined bodi weight and growth pattern. Results of analisys showed that the body weight of chicken was 732,21 g on age of 8 weeks with 10,61 g / day of growth rate. As a result, growth pattern fitted to the body weight – age data from native fowls might suggest us to used intensif farming system in native fowls rearing..